Razvoj riječnog prometa s osvrtom na tehničko-tehnološke značajke - Brkić, Alojz (Promet - Traffic&Transportation, 2012)
River transport in our country, and particularly on the territory of the Republic of Croatia, creates major possibilities for services required for industries in both domestic and international transport. Considering the fact that this aspect of transport is one of the least expensive in the general transport system it should be as soon as possible reinstated an made adequate from the engineering and technological standpoint to realistically take its due place in the transport industry. Drawing a comparison of the construction of the Rhine-Main- Danube Canal to Cherna Voda-Constance and the development of other Adriatic- Danube Basin traffic routes to our actual requirements and reflections upon the condition of development of our waterways, the question is raised on the future of development of our river shipping i. e. construction of the Šamac- Vukovar canal and opening of the Sava river for navigation all the way to Zagreb.